2014
DOI: 10.3402/meo.v19.22623
|View full text |Cite
|
Sign up to set email alerts
|

From student to steward: the Interdisciplinary Program in Neuroscience at Georgetown University as a case study in professional development during doctoral training

Abstract: A key facet of professional development is the formation of professional identity. At its most basic level, professional identity for a scientist centers on mastery of a discipline and the development of research skills during doctoral training. To develop a broader understanding of professional identity in the context of doctoral training, the Carnegie Initiative on the Doctorate (CID) ran a multi-institutional study from 2001 to 2005. A key outcome of the CID was the development of the concept of ‘stewards o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Most scientists agree that communication skills are valuable and that being able to connect with a broad audience is uniquely important (2,12). However, although others have reported that graduate students in various disciplines find engaging in public outreach rewarding (13,15), to the best of our knowledge, this is the first example of a course focusing on public communication skills to enhance graduate student training in physiology.…”
Section: Discussion/conclusionmentioning
confidence: 94%
“…Most scientists agree that communication skills are valuable and that being able to connect with a broad audience is uniquely important (2,12). However, although others have reported that graduate students in various disciplines find engaging in public outreach rewarding (13,15), to the best of our knowledge, this is the first example of a course focusing on public communication skills to enhance graduate student training in physiology.…”
Section: Discussion/conclusionmentioning
confidence: 94%
“…In another season, groups of GST students developed tutorials in their area of computational specialization and taught the tutorials to the entire class (see the Supplemental Material). GST students are encouraged to become stewards of their program and their discipline ( Ullrich et al. , 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…GST students are encouraged to become stewards of their program and their discipline ( Ullrich et al. , 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Освітня програма підготовки аспірантів, орієнтована на здобуття універсальних навичок дослідника, представлена хорватськими авторами [3]. Вчені із США описали міждисциплінарну програму, яка дозволяє сформувати у аспірантів основні професійні навички, необхідні для їх майбутньої успішної кар'єри [4]. Результати наших емпіричних досліджень щодо змісту, форм і методів підготовки молодих науковців представлені у роботі [5].…”
Section: содержательно-операционный компонент готовности будущего доктора философии к исследовательско-инновационной деятельности © 2019unclassified